THE ROLE OF SOCIAL MEDIA IN QUARTER-LIFE CRISIS AMONG EMERGING ADULTS: A SYSTEMATIC LITERATURE REVIEW - Bekti Estu Estu; Novi Hidayat; Iksal Maulana (Universitas Sains Indonesia Publishing, 2026)
Quarter-life crisis is a psychological phenomenon commonly experienced during emerging adulthood. One factor that has been suggested to contribute to this condition is the use of social media. This study aimed to examine the role of social media in quarter-life crisis among emerging adults using the Systematic Literature Review (SLR) approach. The literature search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was conducted across several scientific databases. The identification stage yielded 401 articles, which were subsequently screened according to predefined inclusion and exclusion criteria, resulting in four eligible studies for qualitative synthesis. The findings indicate that three studies reported a positive and statistically significant relationship between the intensity of social media use and quarter-life crisis. In contrast, one study found that the intensity of social media use did not moderate the relationship between religiosity and quarter-life crisis. Overall, the evidence suggests that social media contributes to increased social comparison, heightened pressure to achieve life milestones, and greater anxiety about the future, all of which may exacerbate quarter-life crisis among emerging adults. Therefore, promoting mindful social media use and strengthening protective psychological factors are essential strategies for mitigating the adverse effects of social media on the psychological well-being of emerging adults.